Pengaruh Latihan Plyometric Terhadap Daya Ledak Otot Tungkai Ditinjau dari Panjang Tungkai Peserta Ekstrakurikuler Atletik Sekolah Dasar - Eko Firdaus; Cerika Rismayanthi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to analyze the effect of differences between plyometric box jump and hurdle jump training on improving leg muscle explosive power among elementary school students in athletics extracurricular activities, (analyze the effect of differences between students with long legs and short legs on leg muscle explosive power, and examine the interaction between types of plyometric training (box jump and hurdle jump) and leg length (long and short) on leg muscle explosive power.The research employed an experimental method with a 2x2 factorial design. The population consisted of 24 elementary school students participating in athletics extracurricular activities, selected using purposive sampling. Data were analyzed using two-way ANOVA at a significance level of 0.05 to test both main and interaction effects.The results revealed that plyometric training had a significant effect on leg muscle explosive power (Sig. = 0.012 < 0.05), indicating that both box jump and hurdle jump exercises were effective in enhancing explosive contraction and students’ jumping performance, there was a significant difference between students with long and short legs in terms of explosive power (Sig. = 0.007 < 0.05), in which short-legged students showed more significant results due to mechanical advantages of lower moment of inertia and faster muscle contraction, allowing optimal use of elastic energy, and there was a significant interaction between training type and leg length on leg muscle explosive power (Sig. = 0.002 < 0.05). Short-legged students responded better to box jump training, whereas long-legged students were more suited to hurdle jump training. In conclusion, plyometric training is effective in improving leg muscle explosive power, and anthropometric factors, particularly leg length, should be taken into consideration when selecting training methods to achieve optimal results. Keywords: plyometric, box jump, hurdle jump, leg length, leg muscle explosive power.